Media Audio Dalam Layanan Bimbingan dan Konseling di Sekolah/Madrasah - Nurlatifah, Andar Ifazatul (Madaniyah, 2018)
This paper reviews the use of audio devices in school counseling based on text literature in counseling, education, and communication. It includes definitions, kinds, functions, procedures, positive and negative impacts, and usability of audio devices in counseling. The final result is audio devices increase the effectiveness and efficiency of students development curriculum, responsive services, individual students planning, and system support in school counseling through needs assessing, materials delivering, and activities recording. Counselors technically can use it to play music as emotional stimulus, aesthetic experience, relaxation and imagination stimulus, as self-expression, and as medium of group experiences for counselee.Keywords: audio device; counseling; guidance